The Effect Of Giving Mp-A SI Using The Baby Led Weaning Method On Baby's Weight Babies Aged 9-12 Months In The Patingalloang Community Health Center Working Area - Sumarni Sumarni; Nahira Nahira (Lembaga Pengembangan Kinerja Dosen, 2023)
Nutritional intake plays an important role in optimizing baby's growth and development. The amount of nutritional intake consumed is also influenced by the process of eating activities. The aim of this research is to determine the effect of the Baby Led Weaning Method on baby weight in the Patingalloang Community Health Center Working Area. Quantitative research method with experimental design with a one group pretest-posttest design approach. The research population was toddlers experiencing stunting who met the inclusion and exclusion criteria using purposive sampling techniques. Research results: The intervention group with a sample size of 20 children experienced an average weight gain of 0.85 kg. The control group also experienced an average increase of 0.65 kg with a test value of p value = 0.000, where it was concluded that there was an effect of giving MP-ASI using the Baby Led Weaning Method on the weight of babies aged 9-12 months in the working area of the Patingalloang Community Health Center.